2016
DOI: 10.3892/ol.2016.4943
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effect of deoxypodophyllotoxin induces apoptosis of human prostate cancer cells

Abstract: Abstract. Deoxypodophyllotoxin (DPPT) is extracted and separated from citrus-related plants, including Podophyllum (P.) peltatum, P. pleianthum, P. emodi (also called P. hexandrum) and Diphylleia grayi. DPPT has significant antitumor and antiviral activity. However, due to its strong toxicity and side effects, its use is limited in practical applications. The in vitro antitumor efficacy of DPPT on human prostate cancer (PCa) cells remains to be determined. The present study investigated the anticancer effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…An in vitro study from Hu et al [ 120 ] investigated the cytotoxic effect of DPT (8) on human prostate cancer DU-145 cells and its potential action mechanism. The results revealed that DPT (8) induced cell apoptosis and inhibited cell proliferation.…”
Section: Bioactive Secondary Metabolites From Juniperus mentioning
confidence: 99%
See 1 more Smart Citation
“…An in vitro study from Hu et al [ 120 ] investigated the cytotoxic effect of DPT (8) on human prostate cancer DU-145 cells and its potential action mechanism. The results revealed that DPT (8) induced cell apoptosis and inhibited cell proliferation.…”
Section: Bioactive Secondary Metabolites From Juniperus mentioning
confidence: 99%
“…Detection of high levels of the caspase-3 expression suggests that caspase-mediated pathways were involved in DPT-induced apoptosis. Moreover, the authors suggest that apoptosis was also induced through downregulation of the levels of phosphorylated Akt and activation of the p53/B-cell lymphoma 2 associated X protein/phosphatase and tensin homolog (i.e., Akt/p53/Bax/PTEN) signaling pathway [ 120 ]. Although this work must be emphasized because it exposes a new target involved in the DPT (8) mechanism of action, no control was used nor were IC 50 values against DU-145 cells line presented, which is a misfortune since it decreases the scientific impact of the study.…”
Section: Bioactive Secondary Metabolites From Juniperus mentioning
confidence: 99%
“…DPT, the precursor of podophyllotoxin, is a lignan that has various pharmacological effects [10,11]. In previous studies, DPT has been found to adjust cell growth, proliferation, cell cycle arrest, cancer cell invasion, and metastasis in several different types of cancer cells [12][13][14]. DPT is an aryltetralin cyclolignan structurally closely related to the lignan podophyllotoxin that contains four consecutive chiral centers and four almost planar fused rings and picropodophyllotoxin, an epimer of podophyllotoxin studied in the previous paper [33].…”
Section: Discussionmentioning
confidence: 96%
“…These include anti-inflammatory, antiplatelet aggregation, antiallergic, antiproliferation, antitumor, and antiviral properties [11]. A number of studies have reported that DPT induces apoptosis through cell cycle arrest and caspase-mediated pathways in prostate, gastric, and cervical cancer [11][12][13][14]. However, the question of whether DPT suppresses ESCC by induction of apoptosis has not been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Deoxypodophyllotoxin (DPT) is one of the main active ingredients in herbs like Podophyllum emodi, Anthriscus sylvestris, and Pulsatilla koreana (Wong et al, 2000;Khaled et al, 2013). The lignan compound exhibits various pharmacological activities such as antitumor, antiviral, antiplatelet aggregation, and anti-inflammatory effects (Khaled et al, 2013), among which the antitumor effect has received the most attention and is therefore widely characterized (Kim et al, 2002;Shin et al, 2010;Jiang et al, 2013;Hu et al, 2016;Khaled et al, 2016). In China, a phase I clinical trial for DPT has been approved for patients of lung cancer, gastric cancer, and breast cancer-especially those resistant to paclitaxel and etoposide-in an intravenous formulation of b-cyclodextrin inclusion complex.…”
Section: Introductionmentioning
confidence: 99%